The peacemaker : a biblical guide to resolving personal conflict - Sande, Ken (Grand Rapids, MI : Baker Books, 2004)
Peacemaker Ministries president Ken Sande gives practical biblical advice for conflict resolution that takes you beyond resolving conflicts to true, life-changing reconciliation with family, coworkers, and fellow believers. - Back cover.
In The Peacemaker, Ken Sande presents a comprehensive and practical theology for conflict resolution designed to bring about not only a cease-fire but also unity and harmony.
Part 1. Glorify God -- Conflict provides opportunities -- Live at peace -- Trust in the Lord and do good -- Part 2. Get the log out of your eye -- Is this really worth fighting over? -- Conflict starts in the heart -- Confession brings freedom -- Part 3. Gently restore -- Just between the two of you -- Speak the truth in love -- Take one or two others along -- Part 4. Go and be reconciled -- Forgive as God forgave you -- Look also to the interests of others -- Overcome evil with good -- Conclusion : The peacemaker's pledge.
Includes bibliographical references (pages 306-308) and indexes.
Keywords: Reconciliation -- Religious aspects -- Christianity; Interpersonal relations -- Religious aspects -- Christianity; Conflict management -- Religious aspects -- Christianity; Peace -- Religious aspects -- Christianity